Changes in the Cardiac Index Induced by Unilateral Passive Leg Raising in Spontaneously Breathing Patients: A Novel Way to Assess Fluid Responsiveness - Zhiyong Zhao; Zhiyong Zhao; Zhongwei Zhang; Zhongwei Zhang; Qionghua Lin; Qionghua Lin; Lihua Shen; Lihua Shen; Pengmei Wang; Pengmei Wang; Shan Zhang; Shan Zhang; et al. (Frontiers in Medicine, 2022)
BackgroundEvaluation of fluid responsiveness in intensive care unit (ICU) patients is crucial. This study was to determine whether changes in the cardiac index (CI) induced by a unilateral passive leg raising (PLR) test in spontaneously breathing patients can estimate fluid responsiveness.MethodsThis was a prospective study, and 40 patients with spontaneous breathing activity who were considered for volume expansion (VE) were included. CI data were obtained in a semirecumbent position, during unilateral PLR, bilateral PLR, and immediately after VE. If the CI increased more than 15% in response to the expansion in volume, patients were defined as responders.ResultsThe results showed that a unilateral PLR-triggered CI increment of ≥7.5% forecasted a fluid-triggered CI increment of ≥15% with 77.3% sensitivity and 83.3% specificity with and an area under the receiver operating characteristic (ROC) curve of 0.82 [P < 0.001]. Compared with that for bilateral PLR, the area under the ROC curve constructed for unilateral PLR-triggered changes in CI (ΔCI) was not significantly different (p = 0.1544).ConclusionΔCI >7.5% induced by unilateral PLR may be able to predict fluid responsiveness in spontaneously breathing patients and is not inferior to that induced by bilateral PLR.Trial RegistrationUnilateral passive leg raising test to assess patient volume responsiveness: Single-Center Clinical Study, ChiCTR2100046762. Registered May 28, 2021.